One Health, many approaches: integrated vector management strategies support One Health goals - Tiffin, Hannah S.; Gordon, Jennifer R.; Poh, Karen C. (Frontiers in Insect Science, 2025)
Integrated pest management (IPM) laid the foundation for integrated vector management (IVM) by introducing strategies that prioritize prevention over intervention and the use of diverse management and control tools for arthropod vectors. Both approaches focus on reducing chemical reliance for management of targeted organisms by employing data-driven decisions and incorporating the use of additional non-chemical based management tactics. While IPM and IVM differ in their specific applications and management contexts, many of their fundamental principles remain the same. By diversifying prevention and control options, these management practices support healthier environments, animals, and populace, the three spheres of the One Health paradigm. One Health principles support and highlight the connections between animal, human, and environmental health and how these spheres influence one another. However, the connections and overlapping goals between IVM and One Health are infrequently discussed in tandem. This review will examine the numerous and varied methods of IVM for reducing global disease burden, detail the benefits of using IVM to achieve One Health goals, as well as benefits and considerations to incorporating a One Health lens with IVM.